Answer:
<em>1</em><em> </em><em>second</em><em> </em>
Step-by-step explanation:
<em>16t</em><em>^</em><em>2</em><em>+</em><em>64t</em><em>=</em><em>80</em>
<em>16t</em><em>^</em><em>2</em><em>+</em><em>64t-80</em><em>=</em><em>0</em>
<em>64</em><em>^</em><em>2-4</em><em>(</em><em>16</em><em>)</em><em>(</em><em>-80</em><em>)</em>
<em>9216</em>
<em>-64-96</em>
<em>______</em><em> </em><em>=</em><em> </em><em>-5</em>
<em> </em><em> </em><em> </em><em>32</em>
<em>-64</em><em>+</em><em>96</em>
<em>_______</em><em> </em><em>=</em><em> </em><em>1</em><em> </em><em>sec</em>
<em> </em><em> </em><em> </em><em> </em><em>32</em>
Answer:
see below
Step-by-step explanation:
h(x) = 2x-10
Let x=3
h(3) = 2*3 -10
= 6-10
=4
Let x=-3
h(-3) = 2*-3 -10
= -6-10
=-16
Answer:
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
10*y-(80)=0
Pull out like factors :
10y - 80 = 10 • (y - 8)
Solve : 10 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solve : y-8 = 0
Add 8 to both sides of the equation :
y = 8
Answer:
thank you for the warning the moderators of this website really need 2 get there stuff together
Step-by-step explanation: